유방촬영검사에서 평균유선선량과 장치의 품질관리 실태 - 정홍량; Hongryang Jung; 황수련; Sulyun Hwang; 하본철; Boncheol Ha (Journal of the Korean Society of Radiology, 2011)
본 연구는 39개 1차 의료기관을 대상으로 유방촬영 장치의 정도관리 상태에서 실제 방사선 피폭선량을 측정하였다. 유방촬영 시 1차 의료기관의 방사선 피폭선량의 최적화와 진단참고준위값을 제시하고자 연구한 결과는 다음과 같다. 첫째, 영상의학과와 일반의원으로 구분하여 T-검정분석 결과 mAs는 영상의학과 80.16 mAs, 일반의원 77.22 mAs로 평균 78.58 mAs로 측정되었으며, 공기커마율은 영상의학과 8.94 mGy/mR, 일반의원 6.66mGy/mR로 평균 7.71mGy/mR 측정되었다. 반가층은 영상의학과 0.40 ㎜Al, 일반의원 0.43 ㎜Al로 평균 반가층은 평균 0.42㎜Al 측정되었고, 평균유선선량은 영상의학과 1.09 mGy 일반의원 1.19 mGy로 1.14 mGy로 측정되었다. 둘째, mAs, 반가층, 현상방법, SID를 두 그룹으로 구분하여 평균치를 T-검정 결과 SID에서 유의한 차이가 있는 것으로 나타났고(P<0.05), 영상의학과의 현상방법에서 현상기 사용 1.00 mGy, CR은 1.17 mGy로 mAs에서 유의한 차이가 있는 것으로 나타났다(P<0.05). 셋째, 항목별 상관분석에서는 평균유선선량에서 영상의학과는 mAs가 일반의원은 SID에서는 상관관계의 유의성이 있는 것으로 나타났다(P<0.05), 넷째, 항목별 회귀분석 결과 평균유선선량에서 mAs가 미치는 영향력은 22.7%, SID가 21.7%로 통계적으로 의미가 있었으며(P<0.05), 영상의학과의 평균유선선량에서 mAs가 미치는 영향력은 29.0%, 일반의원은 평균유선선량에서 SID가 미치는 영향력은 29.1%로 가장 많은 영향력이 있는 것으로 나타났다 A purpose of study is to develop optimization and radiation dose exposure reference level by measuring actual radiation dose in condition of quality control of mammography equipment for 39 clinics. The result were as follows First, we measured T-test separating radiology from general clinic. According to the test, mAs was measured at average 78.58 mAs; radiology at 80.16 mAs and general clinic at 77.22 mAs. And, kerma rate was measured at average 7.71 mGy/mR; radiology at 8.94 mGy/mR and general clinic at 6.66 mGy/mR. HVL was measured at average 0.42 ㎜Al; radiology at 0.40 ㎜Al and general clinic at 0.43 ㎜Al. Average glandular dose was measured at average 1.14 mGy; radiology at 1.09 mGy and general clinic at 1.19 mGy. Second, we measured value of mAs, HVL, processing method and so on dividing two groups. And, we compared and analyzed average value measured using T-test. As a result, there was significance level in SID(P<0.05). There was significance level in mAs(P<0.05). Because processor was measured at 1.00 mGy and CR at 1.17 mGy according to the processing method of radiology Third, according to the correlation analysis, radiology had significance level between average glandular dose and mAs and general clinic had significance level between average glandular dose and SID(P<0.05). Forth, as a result of regression analysis, mAs affected 22.7%t of average glandular dose and SID affected 21.7% of average glandular dose, which had significance level(P<0.05). And, mAs affected 29.0% of average glandular dose in radiology and SID affected 29.1% of average glandular dose in general clinic, which was most influential.